Perbedaan Pengaruh Antara SWD dan Mobilisasi Saraf dengan William’s Flexion Exercise Terhadap Kemampuan Fungsional Pasien Nyeri Punggung Bawah Iskhialgia - Lilik Sigit Wibisono; Siti Sundari; Syurrahmi Syurrahmi; Putri Soniatus; Almita Ratu Rifanda (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The purpose: To determine the effect of differences between SWD and neural mobilization with SWD and William’s flexion exercise to improve of functional ability on patient’s with low back pain ischialgia. Design: Two group pretest and posttest design. Participants and interventions: Ten patients with low back pain ischialgia from both sexes were involved (outpatient hospital clinic). Age of the patients between 46 – 65 years. They were divided into two equal groups, Group (I) received SWD and neural mobilization intervention and Group (II) received SWD and William’s flexion exercise. Outcome measure: The Oswestry disability index (ODI) was used to assess changes in perceived disability. The mean differences between week 0 and week 3 were compared across the two treatment groups using Mann-Whitney. Ninety-five percent (95%) confidence intervals (CIs) for the differences between groups were calculated. Results: The results of study revealed that: there was significant difference in functional ability group I (p=0.034) and group II (p=0.038). Howeverthere wasn’t a significant difference between both groups on functional disabilities improvement (p=0.245), so there wasn’t intervention which better of both. Conclusion: It is concluded that SWD addition neural mobilization and SWD addition William’s flexion exercise may be beneficial in the management of patients with low back pain ischialgia to improving of functional ability in two groups.